Tobramycin: efficacy of intensive therapy (Perioperaciina Medicina, 2021)
One of the leading cause of the decrease of treatment efficacy in patient with community-acquired infections in the intensive care department is a spread of antibiotic resistance in main causative agents. Among Gram-negative microorganisms Pseudomonas aeruginosa is one of the leading causative agents, that is related to health service. A review of foreign and domestic literature concerning tobramycin – systemic form use in the current medical practice in the conditions of increasing resistance of microorganisms to the most broad-spectrum antibiotics is presented in the article. Pharmacokinetic and pharmacodynamic characteristics of tobramycin are described, results of clinical trials, that demonstrate an efficacy of its use in the combination with other antibiotics in the life-threatening infections caused by Gram-negative microorganisms are presented in the article.
Keywords: aminoglycosides; tobramycin; Pseudomonas aeruginosa